PENGARUH PENDIDIKAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INGGRIS SISWA (SURVEY PADA SD NEGERI DI KABUPATEN LEBAK) - Bahri, Samsu (Jurnal Pendidikan Dasar Setiabudhi, 2019)
This study aims to analyze the truth of the hypothesis regarding the influence of reading interest andvocabulary mastery on the ability to write text description students. The research hypotheses tested included:1) The Effect of Parental Education and Learning Motivation on students' English learning achievement. 2)the effect of parental education on students' English learning achievement. 3) The effect of learningmotivation on students' English learning achievement. The research method used is observation. Thepopulation of this study was all grade VI students of SD Negeri in Lebak Regency with a sample size of 60students, with a simple random sampling technique. Instrument data about parental education and learningmotivation obtained through questionnaires and English learning achievement were obtained from reportcards. Data analysis uses multiple regression analysis. The results of hypothesis testing obtained thefollowing conclusions: (1) there is a significant influence of parental education and learning motivation onthe learning achievement of English students in class VI at SD Negeri Regency Lebak. This is evidenced bythe value of sig. = 0,000 <0.05 and t arithmetic = 55.905. (2) there is a significant influence of learningmotivation on English language learning achievement of Grade VI students of SD Negeri in Lebak Regency.This is evidenced by the value of sig. = 0,000 <0.05 and t arithmetic = 5.926. (3) there is a significantinfluence of learning motivation on English language learning achievement of Grade VI students of SDNegeri in Lebak Regency. This is evidenced by the value of sig. = 0.001 <0.05 and t arithmetic = 3.570.Keywords: Parental Education, Learning Motivation, English Learning Achievement AbstrakPenelitian ini bertujuan untuk menganalisis kebenaran hipotesis mengenai pengaruh minat baca danpenguasaan kosa kata terhadap kemampuan menulis teks deskripsi siswa. Hipotesis penelitian yang diujimeliputi : 1) Pengaruh Pendidikan Orang tua dan Motivasi Belajar terhadap prestasi belajar Bahasa Inggrissiswa. 2) pengaruh pendidikan orang tua terhadap prestasi belajar Bahasa Inggris siswa. 3) Pengaruh motivasibelajar terhadap prestasi belajar Bahasa Inggris siswa. Metode penelitian yang digunakan adalah observasi.Populasi penelitian ini adalah seluruh siswa kelas VI SD Negeri di Kabupaten Lebak dengan besaran sampel60 siswa, dengan dengan teknik sampling simple random.instrumen data tentang pendidikan orang tua danmotivasi belajar yang diperoleh melalui kuesioner dan prestasi belajar Bahasa Inggris diperoleh dari nilairaport. Analisis data menggunakan analisisregresi ganda. Hasil pengujian hipotesis diperoleh kesimpulansebagai berikut: (1) terdapat pengaruh yang signifikan pendidikanorang tua dan motivasi belajarterhadapprestasi belajar Bahasa Inggris siswa kelasa VI SD Negeri di Kabupaten Lebak. Hal ini dibuktikan dengannilaisig.= 0,000 < 0,05 dan t hitung = 55,905. (2) terdapat pengaruh yang signifikan motivasi belajar terhadapprestasi belajar Bahasa Inggris siswa kelas VI SD Negeri di Kabupaten Lebak. Hal ini dibuktikan dengannilaisig. = 0,000 < 0,05 dan t hitung = 5,926. (3) terdapat pengaruh yang signifikan motivasi belajar terhadapprestasi belajar Bahasa Inggris siswa kelas VI SD Negeri di Kabupaten Lebak. Hal ini dibuktikan dengannilaisig. = 0,001 < 0,05 dam t hitung = 3,570.Kata Kunci : Pendidikan Orang Tua, Motivasi Belajar, Prestasi Belajar Bahasa Inggris